Complications associated with PICC insertion in a hospital for high level of complexity of the city of Medellín (Colombia). - Roldán, S.; Combariza, F.; Gálvez, K.; Palacios, V.; Olaya, V. (Revista Colombiana de Hematología y Oncología, 2017)
Objective. To identify the complications related with peripherally inserted central catheter (PICC).